The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1007/bf00186881
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis of the knee after ACL reconstruction

Abstract: One hundred and fourteen knees with deficiency of the anterior cruciate ligament (ACL) which had undergone reconstruction of the ligament using semitendinosus and gracilis were reviewed at a mean of 61 months after operation. Radiological and clinical evaluation was undertaken. A significant correlation was found between the number of meniscectomies performed in acute cases and those undertaken on the chronic knee. There was also significant correlation between meniscectomy and the Fairbank grading of degenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
102
2
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 10 publications
12
102
2
8
Order By: Relevance
“…As to the radiograph, several studies have reported that, after ACL reconstruction, the progression rate of OA increased (Ferretti et al, 1991;van der Hart et al, 2008). The surgical procedure for the ACL reconstruction may be of importance regarding the risk of eventual developing knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…As to the radiograph, several studies have reported that, after ACL reconstruction, the progression rate of OA increased (Ferretti et al, 1991;van der Hart et al, 2008). The surgical procedure for the ACL reconstruction may be of importance regarding the risk of eventual developing knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…Knee traumas, in particular, represent over 40% of all sports injuries [5][6][7] and often result from traffic accidents with surgical restoration of joint stability not preventing future arthritis development [8][9][10][11]. The incidence of post-traumatic arthritis is therefore high -creating insistent demand for pharmacological intervention, directed at limiting the progression and propagation of destructive processes taking place in the early stages post-injury [2,12].…”
Section: Introductionmentioning
confidence: 99%
“…Restoring knee-joint stability through ACL reconstruction has not been shown to decrease the incidence of posttraumatic OA in this patient population. However, some reports indicate that 50-60% of patients with ACL-reconstructed knees have radiographic evidence of OA after five years [1,3]. These data suggest that something other than, or in addition to, a biomechanical disturbance is responsible for the osteoarthritic changes seen after ACL rupture.…”
Section: Introductionmentioning
confidence: 99%